Psychometric properties of Clinical Learning Environment Inventory and its association with Moroccan nursing students’ satisfaction: A PLS-SEM approach - Khadija Saka; Mohamed-Yassine Amarouch; Mohamed El Amine Ragala; Zarrouq Btissame; Adel Tahraoui; Youness El Achhab; Jaouad El-Hilaly (Belitung Nursing Journal, 2023)
Background: The Clinical Learning Environment (CLE) is integral to pre-registration nursing curricula. Assessing the student’s perceptions of their CLE is essential to adjust clinical placement to trainees’ needs. Clinical Learning Environment Inventory (CLEI) appears to be widely used in measuring CLE, but no previous study has reported a full structural validity and its association with students’ satisfaction in the Moroccan context. Objectives: This study investigated the psychometric properties of the CLEI and its subscales association with Moroccan nursing students’ satisfaction. Methods: The research design was descriptive, cross-sectional, and conducted from March and June 2022 using convenience sampling in three nursing institutes of the Fez-Meknes region of Morocco. The selected sample involved Moroccan nursing students undertaking clinical practice. First, exploratory factor analysis (EFA) was used to determine the factor structure of the pilot sample (N = 143). The second sample (N = 206) was then used to confirm this structure using partial least squares structural equation modeling (PLS-SEM) confirmatory composite analysis (CCA). Finally, using a bootstrapping method, the significance of the structural path was evaluated. Results: The CLEI scale depicted convergent validity (AVE = 0.56 - 0.71), discriminant validity, estimated by the square roots of AVE and bootstrapped HTMT confidence interval, and significant reliability (rhoC = 0.83 - 0.92). Using a bootstrapping approach, structural path significance displayed a substantial association between task orientation and students’ satisfaction (β = 0.29, p <0.001). This ascertains that nurse students need well-planned guidelines from their facilitators in clinical wards. Conclusions: The CLEI instrument revealed adequate psychometric properties and supported its original structure. As a result, the instrument might be used to measure students’ perceptions of their CLE. Task orientation appeared to be the most important factor influencing the students’ satisfaction in CLE.